2019
DOI: 10.1051/0004-6361/201935032
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter spectroscopy and astronomical searches of vinyl mercaptan, C2H3SH

Abstract: Context. New laboratory investigations of the rotational spectrum of postulated astronomical species are essential to support the assignment and analysis of current astronomical surveys. In particular, considerable interest surrounds sulfur analogs of oxygencontaining interstellar molecules and their isomers. Aims. To enable reliable interstellar searches of vinyl mercaptan, the sulfur-containing analog to the astronomical species vinyl alcohol, we have investigated its pure rotational spectrum at millimeter w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…This is consistent with the results of Agúndez et al (2021) toward TMC-1, where the abundance ratio s-H 2 C=CHOH/CH 3 CHO is ∼1. In contrast, Martin-Drumel et al (2019) did not detect vinyl alcohol in the EMoCA survey toward the high-mass star-forming region SgrB2(N2) (Belloche et al 2016), with an abundance ratio s-H 2 C=CHOH/CH 3 CHO≤0.08.…”
Section: Vinyl Alcohol: Comparison With Previous Observationsmentioning
confidence: 66%
See 1 more Smart Citation

Precursors of fatty alcohols in the ISM: Discovery of n-propanol

Jimenez-Serra,
Rodriguez-Almeida,
Martin-Pintado
et al. 2022
Preprint
“…This is consistent with the results of Agúndez et al (2021) toward TMC-1, where the abundance ratio s-H 2 C=CHOH/CH 3 CHO is ∼1. In contrast, Martin-Drumel et al (2019) did not detect vinyl alcohol in the EMoCA survey toward the high-mass star-forming region SgrB2(N2) (Belloche et al 2016), with an abundance ratio s-H 2 C=CHOH/CH 3 CHO≤0.08.…”
Section: Vinyl Alcohol: Comparison With Previous Observationsmentioning
confidence: 66%
“…We also report the detection of both syn and anti conformers of vinyl alcohol (CH 2 CHOH) toward the same cloud. The syn conformer was tentatively detected toward SgrB2(N) by Turner & Aponi (2001), but this detection was never confirmed in higher-sensitivity observations carried out with ALMA (Martin-Drumel et al 2019). More recently, Agúndez et al (2021) have unambiguously identified the syn conformer toward TMC-1.…”
Section: Introductionmentioning
confidence: 95%

Precursors of fatty alcohols in the ISM: Discovery of n-propanol

Jimenez-Serra,
Rodriguez-Almeida,
Martin-Pintado
et al. 2022
Preprint
“…Our results build on top of the studies unveiling the chemistry of sulfur in the ISM. Past and recent interstellar searches of saturated (Linke et al 1979;Kolesniková et al 2014;Rodríguez-Almeida et al 2021) and unsaturated (Fuente et al 2017;Martin-Drumel et al 2019;Cernicharo et al 2021;Rodríguez-Almeida et al 2021) S-bearing molecules present a scenario with many mysteries in their formation routes, each one of them contributing to understanding the amount of elemental sulfur locked in organosulfur compounds (Laas & Caselli 2019). In previous studies Lamberts (2018) showed that hydrogenation to saturation of CS is possible in astronomical timescales, indicating that highly saturated species (such as CH 3 SH or C 2 H 5 SH) must be prevalent in later stages of a molecular cloud life.…”
Section: Discussionmentioning
confidence: 99%
“…The spectroscopy community has already begun to extend the spectral characterization of a number of COMs into the submm domain (e.g., Wehres et al 2018b;Kolesniková et al 2018;Motiyenko et al 2019). But even the extension of the spectroscopy of COMs from the cm range, investigated several decades ago, to the mm range already represents significant progress (e.g., Cernicharo et al 2016;Alonso et al 2016;Martin-Drumel et al 2019).…”
Section: Spectroscopic Identifications Of New Speciesmentioning
confidence: 99%